Dens invaginatus type III: report of a case and 10-year radiographic follow-up - Gonçalves, Andréa [UNESP]; Gonçalves, Marcelo [UNESP]; Oliveira, D. P.; Alves, Nilton [UNESP] (Blackwell Publishing, 2002)
Aim the purpose of this article is to report the 10-year follow-up of a right mandibular central incisor with 'dens invaginatus' that was root filled.Summary 'Dens invaginatus ' is a rare malformation of teeth, probably resulting from an infolding of the dental papilla during tooth development. It has alternatively been called 'dens in dente' and 'dilated composite odontome'. Radiographic examination may clearly demonstrate this feature, although no signs may be recognized clinically. If no entrance to the invagination can be detected and there are no signs of pulp pathosis, then no treatment is required other than fissure sealing of the invagination. In deep invaginations, it is likely that root-canal treatment may be required. Occasionally, when the tooth has an immature root, apexification is necessary. Root-canal treatment of a right mandibular central incisor with 'dens invaginatus ' is described along with 10-year follow-up.Key learning pointsBoth clinical and radiographic examinations are necessary to determine morphological features of teeth before root-canal treatment.Sensibility testing to determine the pulp condition is critical prior to treatment.
Keywords: dens in dente; dens invaginatus; treatment